Influence of vitamin E and vitamin E-selenium combination on arginase activity, nitric oxide level and some spermatological properties in ram semen - Ozer Kaya, Seyma; Gur, Seyfettin; Erisir, Mine; Kandemir, Fatih Mehmet; Benzer, Fulya; Kaya, Emre; Sonmez, Mustafa (Wiley, 2020)
The effects of vitamin E and vitamin E-selenium combination on seminal plasma arginase activity and nitric oxide level and some spermatological properties in rams were investigated in this study. For control group, animals were injected intramuscularly with physiological saline. For vitamin E group, rams were injected intramuscularly with 300 mg/ram vitamin E. For vitamin E + selenium group, animals were injected intramuscularly with 5 ml/ram vitamin E + selenium. The semen was collected by artificial vagina at 1st, 4th, 24th, 48th and 72nd hr after administration in each group. Significant decreases in seminal plasma arginase activity (at 1st, 24th and 48th hr), nitric oxide level (at 72nd hr) and abnormal sperm rate (at 1st, 24th and 72nd hr), and significant increases in semen volume (at 24th hr), semen mass activity (at 24th and 48th hr), sperm motility (at 24th, 48th and 72nd hr) and concentration (at 1st hr) were observed in vitamin E group compared with control group. Similarly, significant increase in semen volume (at 1st, 24th and 48th hr), mass activity, (at 48th hr), motility (at 48th and 72nd hr) and concentration (at 4th, 24th and 48th hr), and significant decrements in abnormal sperm rate (at 1st, 24th, 48th and 72nd hr), seminal plasma nitric oxide level (at 1st, 4th, 24th and 48th hr) and semen pH (at 24th and 48th hr) were detected in vitamin E + selenium group in comparison to the control group. As a result, it is suggested that vitamin E and/or vitamin E + selenium applications may improve reproductive performance.
Keywords: arginase activity; nitric oxide; ram; selenium; semen; Vitamine E